Cognitive studies in virtual reality games - Azura, Binti Zainal. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Generally, this research describes the experimental study that elaborates and analyses the cognitive processes in Virtual Reality (VR) games environment. The aim of this research is to create a human cognitive assessment and learning scenarios that would allow for precise control of complex stimulus representation. The interaction of cognitive processes between user and VR games analyses will then provide a useful integration between users' performance and VR environment in the future. The analysis of experiments results in a proposed of standard user's mental model to represent human cognitive processes as to facilitate VR games future designers in games application for making a meaningful interactive VR application. In addition, the findings of this study are important because it represents more than a simple linear extension of existing computer use. Through the experiments that have been conducted, it is cleared that cognitive processes does affect the player's tasks and it is concerned that they have a typical model of user when performing the task(s).